TRADITION AND MODERNITY IN BELLJ'S POETRY - Martos Carrera, Marco (2006)
In order to offer a general appraisal ofthe poet, the article goes back toBelli' s initial work, running from 1958 to 1969, crucial in defining his mainpoetic lines which tend both to tradition and innovation.